Foraminifera as indicators of environmental changes promoted by dredging in tidal channels from Maricá-Guarapina Lagoonal System, Rio de Janeiro, Brazil - Laut, Lazaro; Pereira, Kettollen; Carelli, Thiago; Belart, Pierre; da Silva, André Luiz Carvalho; Martins, Maria Virginia Alves; Fontana, Luiz (Quaternary and Environmental Geosciences, 2024)
To mitigate the anthropogenic impacts on the coastal lagoons, public managershave been implementing different approaches, such as dredging and opening channels to increase the circulation of the marine waters and improve the system’s environmental quality. This study aims to investigate the effects of these approaches (opening and dredging of channels) in the Maricá-Guarapina Lagoonal System, using the relationship between foraminifera and environmental parameters before (2013) and after (2019) these interventions on the environment. After the interventions, data showed a significant increase in the marine influence on the lagoon system. The effects of seasonality could be identified by the reduction of sandy sediments related to the decrease in rainfall between the two analysed periods. The ecological indexes for foraminifera increased in 2019 due to the higher efficiency of water renewal in the lagoons. Ammonia tepida, Ammonia parkinsoniana and Elphidium excavatum were the most constant species in both sampling periods. Quinqueloculina seminulum was replaced by Ammotium morenoi and Ammotium cassis after the interventions as a result of changes in the distribution of muddy sediments in the lagoons. The Assemblage E. excavatum was correlated with higher salinity levels and showed an extension of its range within the lagoons. The same occurred with the Assemblage Paratrochammina guaratibaensis, which indicated high hydrodynamic. On the other hand, Assemblage A. tepida, related to the most impacted area, was distributed in all the innermost lagoons, and after the dredging its distribution was reduced.